DoN-DataOnNutrition®: A platform for managing nutritional therapy in critical patients and supporting ICU research - Santos, Trícia S.; Souza, Welvis S.; Rodrigues, Milo Raziel S.; Magalhães, Marcos Gabriel de S.; Trindade, Tayana O.; França, Cláudia S. dos S.; Santos, Jane Ennys P. dos; Loureiro, Catarine O.; Pereira, Danielle Christine de O.; O. Junior, Nilson Roberto Ribeiro (Companion Proceedings of the Brazilian Symposium on Computing Applied to Healthcare (SBCAS); 2025: Companion Proceedings of the 25th Brazilian Symposium on Computing Applied to Health, 2025)
Nutritional therapy (NT) in critically ill patients remains a challenge. Hospital malnutrition worsens the condition and negatively impacts patients' health. Information technology (IT) and artificial intelligence (AI) offer promising solutions to optimize NT. The DoN-DataOnNutriton® system integrates clinical and laboratory data, providing real-time recommendations and alerts for risks, non-conformities, and changes in tests. The system's structured database, maintained securely and privately in the cloud, facilitates research and the development of personalized solutions to improve precision nutritional therapy.